Pixelated metasurfaces for linear-polarization conversion and absorption - Agrahari R.; Lakhtakia A.; Kumar Jain P.; Bhattacharyya S. (My University, 2025)
Terahertz metasurfaces with pixelated meta-atoms were designed for linear-polarization conversion and absorption. The differences between the two functionalities emerged from the number and arrangement of metal-dielectric combos patching some but not necessarily every pixel of each meta-atom. A patching arrangement for a meta-atom with (Formula presented.) pixels yielded polarization conversion ratio (PCR) (Formula presented.) over the 10.20–16.08 THz band, whereas another yielded absorptance (A) (Formula presented.) over the 27.67–28.73 THz band. A third patching arrangement delivered both functionalities, albeit in different spectral regimes: high PCR and high A at 13.92 THz and 29.1 THz, respectively. The spatial profiles of the electric and magnetic fields in each meta-atom suffice to explain the display of these functionalities. The generality of the pixelated meta-atom approach was supported by a meta-atom with (Formula presented.) pixels. © 2021 Informa UK Limited, trading as Taylor & Francis Group.